La importancia de los recursos tecnológicos en el proceso de enseñanza y aprendizaje de E/LE para alumnos del 2º año de la enseñanza média de la escuela Vestibulando em Abaetetuba-PA - LOBATO, Arivaldo Robson Jorge (2021)
In the process of learning and learning Spanish we find certain technological resources for information and communication resources to use them in the classes as facilitating means results mainly from the similarity between these two Portuguese and Spanish languages. Teachers who must adapt to the new reality imposed by globalization. Therefore, the teacher needs to recognize what kind of professional society wants and how to carry out in the classroom methodologies that are based on those resources in order to come to contribute to citizenship training, innovating methodologies capable of offering an education more and more quality. In this way, the work stems from the need to show the importance of technological resources both for teachers and for students of middle school education in Abaetetuba –PA. This study is based on the studies of the writers Moran (2004), Lévy (2007, 2011), Brandão (1993), Focking (2011), among others, with the intention of understanding the development of these resources and processes for the purpose propose an application through a positive and peaceful teaching proposal.